(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
A 22 year old man was bitten by a snake on his scrotum. This interesting and unusual case occurred in the rural area of Aligarh district in Uttar Pradesh. The uniqueness of the case lies in the fact that scrotum is a very rare and unusual site for snake bite. Further, with negligible local signs of envenoming the patient was presented with classical signs of neurotoxicity. The authors realised that the case may be brought to the notice of the readers because the scrotal bite by the snake with no local signs of envenomation is the first reported case.